Translation Techniques in Indonesian Subtitle Text Of The Bad Guys Movies - Yoga Pranata, Syam Ramadhani; Hartono, Rudi (Publikasi Indonesia, 2025)
Syam Ramadhani Yoga P, The Translation Techniques In Indonesian Subtitle Text Of (The Bad Guys Movies). A Final Thesis: English Department, Language and Arts Faculty, Semarang State University, 2024. The research is explained about translation technique in focusing on find Indonesian translation subtitle in The bad guys. The researcher takes the whole English text subtitle corpus. The goal of the study is investigated by the researcher using a qualitative approach. By reading both the source and target texts, the researcher looks for translation strategies in the texts, marks, categorizes, and analyzes the data using Molina and Albir's translation technique theories. The researcher employs himself to gather data in one of these multiple processes. The data analysis results indicate that: (1) there were eight translation techniques used in The Bad Guys movie; (2) literal translation was the most popular technique used in the movie; and (3) the researcher divided the literal translation techniques to identify the most common frequency, which turned out to be a simple sentence containing the highest percentage